Engendering an avant-garde : the unsettled landscapes of Vancouver photo-conceptualism - Modigliani, Leah, 1970- (Rethinking art's histories., 2018)
A comprehensive examination of the origins of Vancouver photo-conceptualism. The book employs discourse analysis, feminist critique and settler-colonial theory to analyse the landscapes of Jeff Wall, Ian Wallace, Marian Penner Bancroft, Liz Magor and others.